The awareness of cultural dance of East coast using advertising campaign / Mohd Fazlee Ibrahim - Ibrahim, Mohd Fazlee (Faculty of Art and Design, 2012)
Culture Dance of East coast usually performed in choosing social gatherings such as weddings, circumcision, New Year celebrations and other festivals and events. Performances shown are a combination of a form of dance, singing and musical instruments unique strain, What's more interesting to talk about cultural dance in the east coast is unique in terms of presentation and the message conveyed and reinforced with Islamic art as well as highly respected as having values that can be an example for everyone.This academic writing is about awareness of cultural dance of east coast using advertising campaign. From this academic writing, the researcher has to study about what the cultural dance of east coast. The researcher also does the literature searching to gain more information about cultural dance. After the researcher will make and finding from the data that researcher get and finally conclusion and recommendations base on the finding. In this academic writing divided into four chapters. The first chapter is about background of research. This chapter is about the overview of the background research based on literature reviews. The second chapter is about objective and research methodology. This section sets forth the research objectives to be attained and with appropriate methodology to be undertaken for research project. For chapter 3 is about analysis and finding. This section provides the discussions based on the original data obtained from research method. The final chapter is about conclusion and recommendation. This section is highlights the conclusion, which is drawn in line with the objectives, and the development of practical recommendations based on the relevant research findings.